Philippine regional profiles 1996 - Pascual, Ruben Jimenez; Belgosa Business Communications (Makati Belgosa Business Communications, 1996)
Contents: Overview of the Philippines. Features of the specific region. Directories.
Purpose: A series of five yearbooks, each pertaining to the economics, Tourism and business aspects of a region in the Philippines. It also contains directories and yellow pages, as well as detailed descriptions of some areas and issues for each region.
"The Philippine Regional Profile (PRP) is a tribute to all those who have such a monumental turnaround possible: the government, for its untiring effort to make life a little better for Filipino: the private sector, for its unflagging belief in the potentials of the nation; and the people, for their continued faith in the democratic way of life." "This is a five-volume documentation of the opportunities which such changes have opened up to the entrepreneur."
Keywords: Central places -- Philippines -- Guidebooks; Philippines -- Economic conditions -- Directories; Philippine provinces -- Economic conditions